Analisis perbandingan kinerja keuangan provinsi di Pulau Jawa dan Pulau Sumatera - Muhammad Hamdan Sayadi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2020)
The local governments are expected to be able objectify the local budget, especially the revenue that becomes the main source to objectify the expenditure budget. Local governments can be autonomous if its can maximize their potency, especially the local revenue. This paper aims to analyze the level of regional financial dependence and degree of decentralization in the provinces which is located in the Sumatera island and Java with the comparison of financial performance between the provinces. This paper used the method of quantitative descriptive with the ratio of regional financial dependence and degree of decentralization as the analysis tools. The results indicated that financial performance of provinces in the Java island much better than provinces in the Sumatera island because its had much better the realization of local revenue. The factor that affecting financial performance of provinces in the Java island much better was the good ability to acquire local revenue so that it can make very low level of regional financial dependence to the central government and very good degree of decentralization